Effect of Axial Clearance on Volumetric Efficiency of Non-circular Planetary Gear Hydraulic Motors - Li Xiang; Peng Xianlong (Jixie chuandong)
Replacing the hydraulic oil in hydraulic motors with the natural water will lead to an increase in the leakage of the wheel train and a decrease in the volumetric efficiency of motors. In order to improve the volumetric efficiency of the non-circular planetary gear hydraulic motors, the influence of axial clearance between the wheel train and the distribution plate on the volumetric efficiency of the motor is quantitatively analyzed. Firstly, according to the principle of the gap leakage in the rotating plane and the friction force in the fluid, the leakage and power loss formula between the wheels were derived, so as to calculate the optimal solution of the axial clearance of the motor under 30 MPa pressure difference. Secondly, on the basis of considering the manufacturing error, based on the dynamic grid and user-defined function (UDF) programming technology, the leakage amount and volumetric efficiency of the motor under different axial clearances were detected and analyzed, and the theoretical volumetric efficiency of the motor under the same conditions was calculated. The two were compared to obtain the change trend and the minimum value of motor volumetric efficiency under different working conditions. The results show that from the calculation results of selecting the axial clearance value, when the flatness of the wheel is 0.01 mm, the volumetric efficiency of the motor is not less than 77.28% within the working pressure difference of 30 MPa. It provides a basis for the structural improvement of subsequent motors.